Stenosis of the spinal canal of the thoracic spine in a patient with autosomal dominant osteopetrosis type 2 - A. A. Vishnevskiy (Исследования и практика в медицине, 2018)
The presented clinical observa on of a 41-year-old pa ent with an autosomal dominant form of osteopetrosis type II is interes ng not only from the point of view of the complexity of diagnosis of a rare genetic disease complicated by spinal stenosis, but also to determine the tactics of treatment. The patient was examined and treated by phthisiatricians. Histological examina on of the material obtained with trepanobiopsy showed dystrophic changes in bone tissue and poor inﬁ ltra on with lymphocytes; data for tuberculosis of the spine was not revealed. Taking into account the pronounced neurological disorders on the background of spinal cord compression, as well as the instability of the spine, the patient was carried out pallia ve surgery (open biopsy with decompression of the spinal canal, posterior laminar ﬁ xa on of ThVIII—LII and anterior ﬁ xa on of ThVIII–XII combined  tanium implant).  Histological examina on of tissues obtained by open biopsy allowed to suspect a rare disease and ﬁ nally verify the diagnosis after genetic examina on.